VITAMIN D STATUS IN A HEALTHY TUNISIAN POPULATION - BAHLOUS, Afef; KRIR, Asma; MRAD, Mehdi; Mouna, BOUKSILA; Safa, KALAI; Osman, KILANI; Elhem, CHEOUR EL KATEB; Nizar, LAADHARI (Journal of Medical Biochemistry, 2022)
Vitamin D deficiency is one of the most common medical conditions worldwide. In Tunisia, several studies evaluated Vitamin D status, but this was concerning specific populations (pregnant women, obese or diabetic patients and children with asthma). The only study that evaluated Vitamin D status in a healthy Tunisian population was conducted by Meddeb and al. in 2002. The update of data available, based on the currently recommended limits, is necessary. This study aimed to estimate the prevalence of hypovitaminosis D in a healthy Tunisian population, and correlate the values with potential risk factors.It was conducted on 209 Tunisian healthy subjects. Data collected included clinical characteristics and dietary intakes. We measured 25-hydroxyvitamin D (25(OH)D), parathyroid hormone (PTH), glycemia, creatinine, calcium, phosphorus, proteins and alkaline phosphatase levels. Hypovitaminosis D was retained for 25(OH)D concentrations
Keywords: Healthy volunteers; Parathyroid hormone; Prevalence; Tunisia; Vitamin D deficiency